Analisis Hubungan Tingkat Pengetahuan Tentang COVID-19 Dan Penggunaan Imunbooster Karyawan PT Phapros Tbk Semarang - Suwarni, Sri; Aryanti, Destryana; Ayuningtyas, Nurista Dida; Ikhsan, Muhammad; Wulandari, Ratna (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Corona virus Disease 2019 (COVID-19) as a new type of disease that has never been identified before in humans with signs and symptoms including symptoms of acute respiratory disorders such as fever, cough and shortness of breath. COVID-19 can be prevented by improving the body's resistance to respiratory infections. Knowledge is an important domain for the formation of a person's behavior because actions based on knowledge will be more important than actions or behaviors that are not based on knowledge. This study aims to determine the relationship between the level of knowledge about COVID-19 and the use of Immunbooster as a form of infection prevention for employees at PT Phapros Tbk. The research method carried out was descriptive-analytic with a crosssectional research design. The sample in this study was employees at PT Phapros Tbk who met the inclusion and exclusion criteria based on purposive sampling method. For data in this study using primary data from research questionnaires filled out online. Data analysis of the results of the study was carried out using Spearman's rank correlation test. The results showed that there is a relationship between the level of knowledge of COVID-19 and the use of Immunbooster in employees of PT Phapros Tbk Semarang. as evidenced by the spearman's test value obtained value of 0.000 <0.050. The strength of the relationship is moderate as seen from the correlation coefficient value of 0.589 and the test results produce a correlation coefficient value has a positive direction, so it can be said that if COVID-19 knowledge increases, the behavior of using immunbooster will also increase or get better.